2016
DOI: 10.1016/j.ajog.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of gestational age using newborn screening analyte data

Abstract: Metabolic gestational dating is accurate for the prediction of gestational age and could have value in low resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 37 publications
(37 reference statements)
3
58
0
Order By: Relevance
“…The full prediction model had an overall RMSE of 1·04 weeks, and was capable of providing accurate estimations of gestational age to ± 1 or ± 2 weeks of true gestational age in 68·7%, and 95·3% of the cohort, respectively. Consistent with our previous findings (Wilson et al, 2016), performance of all linear regression models was diminished in SGA10 infants. Comparison of linear regression model performance characteristics by gestational age is provided in Table 3.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The full prediction model had an overall RMSE of 1·04 weeks, and was capable of providing accurate estimations of gestational age to ± 1 or ± 2 weeks of true gestational age in 68·7%, and 95·3% of the cohort, respectively. Consistent with our previous findings (Wilson et al, 2016), performance of all linear regression models was diminished in SGA10 infants. Comparison of linear regression model performance characteristics by gestational age is provided in Table 3.…”
Section: Resultssupporting
confidence: 92%
“…We used the same data partitioning strategy described previously (Wilson et al, 2016). In brief, the newborn cohort was divided into three dataset subsamples; one for model development, one to independently validate the choice of terms included in the final model, and one to independently test performance of the final model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well established that NBS metabolites including amino acids and acylcarnitines vary according to gestational age and birth-weight. (6-10) Gestational age and newborn weight as measures of developmental immaturity have long been used to aid in the determination of risk for acquired diseases of prematurity like NEC. As an alternative, NBS panels may be used to identify a predisposing metabolic phenotype that is associated with an acquired disease of prematurity such as NEC.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings demonstrated that this reference model was capable of discriminating between categories of term and preterm birth with robust predictive ability and could also accurately classify infants across a dichotomous preterm birth threshold of 34-weeks gestational age. 13 The utility of newborn metabolic profiles for postnatal gestational dating has also been confirmed by others. 14 15 Our work suggests potential value in using dried blood spot-derived analytes for the postnatal assessment of gestational age.…”
Section: Key Questionsmentioning
confidence: 69%